Agriculture, health, and wealth convergence: bridging traditional food systems and modern agribusiness solutions. (16th December 2014) - Dubé, Laurette; Webb, Patrick; Arora, Narendra K.; Pingali, Prabhu
Abstract : The causes of many vexing challenges facing 21st‐century society are at the nexus of systems involved in agriculture, health and wealth production, consumption, and distribution. Using food as a test bed, and on the basis of emerging roadmaps that set achievable objectives over a 1‐ to 3‐year horizon, we introduce this special feature with convergence thinking and practice at its core. Specifically, we discuss academic papers structured around four themes: (1) evidence for a need for convergence and underlying mechanisms at the individual and societal levels; (2) strategy for mainstreaming convergence as a driver of business engagement and innovation; (3) convergence in policy and governance; (4) convergence in metrics and methods. Academic papers under each theme are accompanied by a roadmap paper reporting on the current status of concrete transformative convergence‐building projects associated with that theme. We believe that the insights provided by these papers have the potential to enable all actors throughout society to singly and collectively work to build supply and demand for nutritious food, in both traditional and modern food systems, while placing the burdens of malnutrition and ill health on their core strategic agendas.